If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -9y + -10 = -5y + 14 Reorder the terms: -10 + -9y = -5y + 14 Reorder the terms: -10 + -9y = 14 + -5y Solving -10 + -9y = 14 + -5y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '5y' to each side of the equation. -10 + -9y + 5y = 14 + -5y + 5y Combine like terms: -9y + 5y = -4y -10 + -4y = 14 + -5y + 5y Combine like terms: -5y + 5y = 0 -10 + -4y = 14 + 0 -10 + -4y = 14 Add '10' to each side of the equation. -10 + 10 + -4y = 14 + 10 Combine like terms: -10 + 10 = 0 0 + -4y = 14 + 10 -4y = 14 + 10 Combine like terms: 14 + 10 = 24 -4y = 24 Divide each side by '-4'. y = -6 Simplifying y = -6
| 1.5x+1.3=.25x-1.16 | | l+41/2=5 | | 2x+79=8x+3 | | -1+5(4n+3)=2(4n-5)+6 | | 2p-14=2p+10 | | 6X=7X-1 | | 7=(10+x)/2 | | -3=(-3+x)/2 | | 3*2-2(11-8)*2=36x | | 4a-4=a+5 | | 11=(12-x)/2 | | 6+9(n-1)=3(-3n-4)-6 | | 4=(4-x)/2 | | 2x+7y-9z= | | 2=(6+x)/2 | | a+3b+80+90=100 | | -5w-14=-7w | | 8(x-1)+36=-3(2x+5) | | 1=(-3+X)/2 | | 7(x^2+9)=35 | | 3x-9=3(2x-6) | | 1=-3+X/2 | | xy-1=3y | | 4e-4=2e+8 | | X-(1/y)=3 | | x/15-11 | | -0.5(y-12)=-0.1(y+1) | | 0=2x^2-5x+3 | | 3x^-4/27x^2 | | 1/2x+5/3=-3/2x-7/3 | | 2(x-5)=x+5x | | (x^2-4x+4)/(x^2+4x-12)*(2x+12)/(6x^2-13x+2) |